Personal well-being and financial threats in Peruvian adults: The mediating role of financial well-being - Estela-Delgado, Bertha; Montenegro, Gilmer; Paan, Jimmy; Morales-García, Wilter C.; Castillo-Blanco, Ronald; Sairitupa-Sanchez, Liset; Saintila, Jacksaint (Frontiers in Psychology, 2023)
Crises negatively affect the economy of a country, increasing financial risk, as they affect work activities and the well-being of the population. This study aimed to examine the mediating role of financial well-being in the relationship between personal well-being and financial threats. A predictive cross-sectional study was conducted. The variables analyzed were personal well-being, financial threats, and financial well-being. A total of 416 Peruvian adults from the three regions of Peru participated. The mean age was M = 35.36, SD = 8.84, with a range of 19–62 years. To represent the statistical mediation model, a structural equation model (SEM) was used. The analysis showed that the variables were significantly related (p < 0.001). The theoretical model indicated a perfect mediation, also obtaining a good fit, χ2(168) = 394.3, CFI = 0.931, RMSEA = 0.057, SRMR = 0.062. The study showed that personal well-being serves as a basis for promoting financial well-being and this contributes to the reduction of financial threats.